The Dynamics of Marriage Law in Islam: Between Tradition and State Regulations - Noferiadin, Noferiadin; Marwendi, Reza Okva (Zabags International Journal of Islamic Studies, 2024)
Marriage law in Islam is a fundamental component of fiqh al-munakahat that governs the legal and spiritual aspects of the marital relationship. In practice, this body of law undergoes dynamic shifts due to the intersection of religious norms, local traditions, and state regulations. This article aims to examine how Islamic marriage law is understood and applied in contemporary contexts, with particular attention to the roles of tradition and state intervention through legislation. The research employs a literature review method, drawing upon classical Islamic jurisprudence, Indonesian legal statutes, and contemporary academic studies. The findings reveal both tensions and harmonization between fiqh and state regulations, especially concerning issues such as minimum age for marriage, guardianship (wali), and marriage registration. The adaptation of Islamic law to the sociopolitical context of the state emerges as a critical factor in developing a fair and applicable family law system